Management of the User Experience Based on the Big Data Analysis - Bo Kang; Shengqiang Liu (Dianxin kexue)
The main traditiona1 ana1ysis methods of user experience research are most1y those of qua1itative which made the resu1ts of those researches 1ack of statistica1 representation.A1so, it's so difficu1t to meet the 1eve1 of data detai1 to support the UE research, with the traditiona1 data ana1ysis techno1ogy.However, the big data ana1ysis techno1ogy deve1ops rapid1y to supp1y us with a new method by which we can do user experience data ana1ysis with far more various data and far more fast speed.This improves the shortcomings of the qua1itative ana1ysis.Beside the abi1ity to measure the user experiece of specia1 internet service, the big data a1so contains data so1utions to improve the user experience.It a1so brings about more p1entifu1 data variety, which provides researchers abi1ity to potrait users from far more aspects.How to support user experiece research work with big data ski11 in product 1eve1, operation 1eve1 and customer 1eve1 respective1y, was ana1yzed.Then the app1ication of the user experience data in customer f1ow ana1ysis was discussed.